Critical evaluation on the ecosystem service levels of provincial capital cities along the Yellow River Basin - Jia, Haifa; Wang, Tianyou; Liang, Pengyu; Zhang, Jianxun; Zhang, Runhao (Frontiers in Environmental Science, 2025)
A comprehensive understanding of the spatiotemporal changes and influencing factors of ecosystem service levels is crucial for regional sustainable development and coordination. The Yellow River Basin faces challenges such as ecological degradation due to uneven regional burdens. This study constructed an ecosystem service evaluation framework based on five dimensions. A combined weighting model was used to assess the ecosystem service levels, spatiotemporal characteristics, and influencing factors of nine provincial capital cities in the Yellow River Basin from 2010 to 2020. The results indicated that: (1) There were notable differences in ecosystem service levels among cities in the Yellow River Basin. The first category of cities, rich in tourism resources, exhibited high ecosystem service levels. The second category of cities, currently undergoing industrial green transformation, urgently needed to achieve a balance between economic development and ecological protection. The third category of cities faced challenges due to poor socioeconomic conditions and limited resources. (2) Resource and energy use, Ecological environmental protection, and Socioeconomic development were the most significant dimensions influencing ecosystem service levels. (3) Indicators such as per capita disposable income, per capita road area, urban green coverage, electricity consumption per unit of GDP, and the number of higher education institutions had a considerable impact on ecosystem service levels. This study suggests optimizing the energy structure, promoting clean energy development, supporting industrial green transformation, and strengthening infrastructure to enhance and protect ecosystem services in the Yellow River Basin.